2001
DOI: 10.1143/jjap.40.l1003
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation Effect of Silicon Substrates due to Quinhydrone/Ethanol Treatment

Abstract: A new technique of surface passivation of silicon substrates by quinhydrone/ethanol treatment has been investigated. To estimate the surface passivation effect, the lifetimes of the silicon substrates were measured using the microwave photoconductive decay method. The measured lifetimes were dependent on quinhydrone concentration and passivation time. The 0.01 mol/dm3 quinhydrone/ethanol treatment showed a good passivation effect, and a very low surface recombination velocity was obtained. The quinhydrone/etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…Typically values of S eff for iodine/ethanol passivated surfaces are in the 10-50 cm/s range [25]. Finally, typical values of about 10 cm/s were usually measured for quinhydrone/methanol passivated Si surfaces (the strategy used in this paper); being the lowest S eff reported 4.2 cm/s for a Fz Si wafer [20]. Accordingly, it cannot be assumed a constant S eff for all the samples, since it will be deeply modulated by the surface preparation and the wafer properties;…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Typically values of S eff for iodine/ethanol passivated surfaces are in the 10-50 cm/s range [25]. Finally, typical values of about 10 cm/s were usually measured for quinhydrone/methanol passivated Si surfaces (the strategy used in this paper); being the lowest S eff reported 4.2 cm/s for a Fz Si wafer [20]. Accordingly, it cannot be assumed a constant S eff for all the samples, since it will be deeply modulated by the surface preparation and the wafer properties;…”
Section: Discussionmentioning
confidence: 75%
“…Before performing minority carrier lifetime measurements, wafer surfaces were passivated in order to reduce the surface recombination and enable an accurate bulk material minority carrier lifetime measurement. For wafers processed only under H 2 (no P diffusion and thus, no emitter), samples were dipped in HF and then passivated using a 0,05M quinhydrone-methanol solution as the passivating agent [20]. For samples treated under phosphine, surface layers were removed with an acidic etch consisting in a HNO 3 :H 2 O:HF solution (to eliminate the P-diffused layer) and then were passivated using the above mentioned wet method.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of passivation, it was shown that lifetime values measured after HQ-methanol treatment surpass those obtained with ethanol, or after iodine-methanol passivation. 38 The HQ-MeOH treatment also yields the strongest surface dipole, according to Kelvin probe measurements, even though the length of the methoxy moiety and of the resulting molecular layer is only 3-4 Å.…”
Section: Surface Dipolementioning
confidence: 94%
“…In addition, at least 1 urn of Si surface material was stripped away for ensuring a clean surface. The etched sample was then passivated in a 0.05M quinhydrone-methanol solution bath [10]. As shown in Table I, the minority carrier lifetime suffers a reversible degradation-recovery process during the epitaxial growth process.…”
Section: Methodsmentioning
confidence: 99%